The growth performance of Kandelia candel hypocotyl cuttings seedlings for mangrove rehabilitation in Indonesia - LEFDI AGUNG NUGRAHA; CECEP KUSMANA; ADISTI PERMATASARI PUTRI HARTOYO (Society for Indonesian Biodiversity, 2024)
Abstract. Nugraha LA, Kusmana C, Hartoyo APP. 2024. The growth performance of Kandelia candel hypocotyl cuttings seedlings for mangrove rehabilitation in Indonesia. Biodiversitas 25: 2683-2695. Kandelia candel (L.) Druce is one of the mangrove species threatened with extinction and continues to decline in number yearly in Indonesia. Effective and efficient propagation techniques are urgently needed to reduce the risk of extinction and accelerate the rehabilitation of this mangrove species. This study aimed to analyze the growth performance of K. candel hypocotyl cuttings and determine the best combination treatments. The type of this study was experimentally carried out in a greenhouse. The experimental design was a completely randomized three-factor factorial design with three factors and three replications for each factor: hypocotyl cuttings, planting media, and growth regulators. Based on the variance test resulted in the interaction between the hypocotyl cutting, planting media, and plant growth regulator had a significant effect on seedling height, number of leaves, total weight biomass, sturdiness quotient, and Dickson Quality Index at the 5% test level. The experiment was a success, with all combinations of treatments showing a survival rate of 100%. The best growth of hypocotyl cuttings was found by combining the bottom part of hypocotyl, mud + sand planting media, and a plant growth regulator of 15,000 ppm. The hypocotyl-cutting method can be an alternative method to provide quality seedlings for mangrove rehabilitation activities.